Hemi-methylated DNA opens a closed conformation of UHRF1 to facilitate its histone recognition - Jian Fang (Nature Portfolio, 2016)
UHRF1 is involved in the maintenance of DNA methylation, but the regulatory mechanism of this epigenetic regulator is unclear. Here, the authors show that it has a closed conformation and are able to make conclusions about the mechanism of recognition of epigenetic marks.